2019
DOI: 10.25259/apos-11-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two polishing systems on color and surface roughness of feldspathic porcelain following orthodontic bracket debonding and composite resin removal

Abstract: Objectives Orthodontic bracket removal from a porcelain crown can roughen the surface and lead to plaque accumulation, discoloration, and esthetic problems. Porcelain polishing after debonding is one strategy to decrease such consequences. This study aimed to compare the efficacy of two polishing systems (Sof-Lex discs and Meisinger polishing system) for correction of surface roughness and discoloration of porcelain after orthodontic bracket debonding. Materials and Methods Twenty porcelain blocks were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Sasany et al [29] recommended polishing with the Sof-Lex system and opinioned that the smoothness and color stability are material and surface treatment dependent. Ameli et al [55] reported that debonded surface polishing with flexible discs results in a porcelain color closer to the baseline.…”
Section: Discussionmentioning
confidence: 97%
“…Sasany et al [29] recommended polishing with the Sof-Lex system and opinioned that the smoothness and color stability are material and surface treatment dependent. Ameli et al [55] reported that debonded surface polishing with flexible discs results in a porcelain color closer to the baseline.…”
Section: Discussionmentioning
confidence: 97%
“…14 Nonetheless, orthodontic bracket bonding on ceramic restorations may increase the surface roughness (due to surface treatment or residual resin removal), change the esthetic appearance of restoration, decrease its longevity, enhance plaque retention, leading to periodontal problems and restoration discoloration. 15 Since zirconia is devoid of glass phase, hydrofluoric acid cannot be used to enhance its bond strength. 16 The suggested strategies for surface treatment of zirconia to enhance its bond strength include airborne particle abrasion (APA), silica-coating, and laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…16 The suggested strategies for surface treatment of zirconia to enhance its bond strength include airborne particle abrasion (APA), silica-coating, and laser irradiation. 16 The effect of different surface treatments in the process of orthodontic bonding, and orthodontic treatment in general, on color parameters and color stability of enamel, [17][18][19][20][21][22][23][24] and feldspathic porcelain 15,[25][26][27] has been previously studied. To the best of the authors' knowledge, no previous study has addressed the effect of orthodontic treatment on color parameters of zirconia restorations.…”
Section: Introductionmentioning
confidence: 99%